2017
DOI: 10.1073/pnas.1621178114
|View full text |Cite
|
Sign up to set email alerts
|

Massive horizontal transfer of transposable elements in insects

Abstract: Horizontal transfer (HT) of genetic material is central to the architecture and evolution of prokaryote genomes. Within eukaryotes, the majority of HTs reported so far are transfers of transposable elements (TEs). These reports essentially come from studies focusing on specific lineages or types of TEs. Because of the lack of large-scale survey, the amount and impact of HT of TEs (HTT) in eukaryote evolution, as well as the trends and factors shaping these transfers, are poorly known. Here, we report a compreh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
242
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(263 citation statements)
references
References 45 publications
18
242
2
1
Order By: Relevance
“…More recently, transposon silencing has proved to be closely related to epigenetic mechanisms including small RNA molecules (siRNA and piRNA) and methylation that control transposon transcription and transposition (Rigal & Mathieu, 2011;Bucher et al, 2012). Thus, in order to escape the host genome selection pressure, MLEs may invade new host genomes by horizontal transfer (HT) as described in several insects (Lampe et al, 2003;Panaud, 2016;Peccoud et al, 2017 The transcriptome shotgun assembly (TSA) of the orange wheat blossom midge Sitodiplosis mosellana (Diptera: Cecidomyiidae) was also used to search for irritans-like elements similar to those in M. destructor. The S. mosellana transcriptome is available in GenBank (NCBI Bioproject PRJNA192921) and consists of 24383 complementary DNA (cDNA) contigs.…”
Section: Data Sourcesmentioning
confidence: 99%
“…More recently, transposon silencing has proved to be closely related to epigenetic mechanisms including small RNA molecules (siRNA and piRNA) and methylation that control transposon transcription and transposition (Rigal & Mathieu, 2011;Bucher et al, 2012). Thus, in order to escape the host genome selection pressure, MLEs may invade new host genomes by horizontal transfer (HT) as described in several insects (Lampe et al, 2003;Panaud, 2016;Peccoud et al, 2017 The transcriptome shotgun assembly (TSA) of the orange wheat blossom midge Sitodiplosis mosellana (Diptera: Cecidomyiidae) was also used to search for irritans-like elements similar to those in M. destructor. The S. mosellana transcriptome is available in GenBank (NCBI Bioproject PRJNA192921) and consists of 24383 complementary DNA (cDNA) contigs.…”
Section: Data Sourcesmentioning
confidence: 99%
“…With this aim in mind, we recently conducted a systematic analysis of HTT among all 195 insect species whose genome sequences were publicly available . Our analysis showed that at least 2248 HTT events occurred among these insects in the last 10 million years.…”
Section: Introductionmentioning
confidence: 99%
“…DNA, however, can also change significantly by mechanisms such as mobility of transposable elements (DNA transposons and retrotransposons). Transposable elements can be regarded as capsid‐free viruses that are trapped within host cells but occasionally can be transferred between different cellular organisms …”
Section: Beyond Darwin?mentioning
confidence: 99%